Aprendiz de professora : as narrativas sobre o processo de constituição da identidade docente dos licenciandos de Matemática - Martins, Rosana Maria (2012)
This research is linked to the Graduate Program in Education UFMT, Campus Rondonópolis. Consisted in a study focused on the investigation of the writings themselves - with memorials training - practical training as a teacher. Inserted in the qualitative approach works with autobiographical narratives. For its development, it has taken up as basis readings of productions that deal with memorials in the constitution of teaching, with the aim of contributing to and reflections that are being developed in Brazil in recent years, especially in the field of mathematics education. As further research in this area, this research focuses on the formation of teaching identity construction with students of Bachelor Course of Mathematics, class of 2009, UFMT, Campus Rondonópolis (CUR) and is part of a larger project approved by the Observatory for Education between the Pontifical Catholic University of São Paulo (PUC-SP) and UFMT. The teaching identity is understood in this research, as a movement of constant tension of the interaction between the subject and their individual experiences and professional, but within a continuum, since the construction of professional identity is movement, is timeless and constant. Worth reporting that this study stands out by investigating subjects without experience in teaching and expressing the memorials, perceptions of their teacher training course. The goal of research is to Analyze the evidence of teaching identity construction of undergraduates in formation in the Course of Mathematics UFMT / CUR. Adopted as research questions: Is there evidence of constitution of teaching identity in narratives (auto) biographies of Undergraduates in Mathematics? How to present themselves personal and educational trajectory of these future teachers? What undergraduates indicate as foundational aspects for its teacher training, from training experiences offered by the Mathematics Course CUR / UFMT? What experiences and practices are mobilizing more reflections on the future profession? The data, collected between 2009 to 2012, showed that subjects describe themselves forming a professional identity in teaching formal and informal spaces, which are influenced by models that marked their schooling. Explain, yet, they want to be teachers, emphasizing the importance of participating in projects oriented, value disciplines that involve practical rationality, because they believe that they allow the redefinition of pedagogical practice. Finally, I hear one of the guys from the narrative analysis, comprising diachronically its formation process, ie, the formation of identity in teaching mathematics. The research also reveals to analyze the memorial of a graduate student in degree over the four years of training, the process of becoming a math teacher occurs in alternating movements, through former teachers and models for other forms of identification, including family and friends, for reflections on practices experienced in Pibid (Institutional Scholarship program Initiation to Teaching) and especially on stage.